Teacher and Student Engagement on Social Media: Its Impact on Learning and Students' Social Life: A Literature Review - Adi Saputra, Surya (Journal of Foundational Learning and Child Development, 2025)
Purpose of the study: This systematic literature review examines the multifaceted relationship between teacher-student social media engagement and its dual impact on academic learning outcomes and students' social development. The study aims to synthesize existing research to identify patterns, contradictions, and gaps in understanding how educational social media interactions influence both pedagogical effectiveness and students' social well-being. Materials and methods: A comprehensive systematic review methodology was employed, analyzing 87 peer-reviewed studies published between 2010 and 2024. Studies were identified through structured database searches in Web of Science, ERIC, Scopus, PsycINFO, and Education Source using predetermined inclusion criteria. Data extraction focused on social media platforms used, interaction patterns, pedagogical approaches, learning outcomes, social-emotional effects, and ethical considerations. Results: The analysis revealed four major themes: (1) platform-specific pedagogical effectiveness with higher engagement rates on interactive multimedia platforms; (2) correlation between structured social media integration and improved learning outcomes; (3) bidirectional influence between academic social media use and students' broader digital social lives; and (4) significant disparities in digital literacy and access affecting engagement patterns. The findings indicate that teacher-moderated social media interactions with clear educational objectives show positive learning outcomes, while unstructured engagement demonstrates inconsistent results. Conclusions: Teacher-student social media engagement presents substantial opportunities for enhanced learning when implemented with intentional pedagogical frameworks, proper boundaries, and digital literacy support. However, careful attention to ethical considerations, privacy concerns, and potential negative impacts on students' social development is essential. Educational institutions would benefit from developing comprehensive social media policies that balance academic innovation with student well-being.